Perception of Physical Education Teachers on Adaptive Physical Education In Inclusive School - Donni Prakosha; Agus Kristiyanto; Gunarhadi Gunarhadi; Abdul Salim; Sunardi Sunardi (International Journal of Pedagogy and Teacher Education, 2018)
Physical education is an important thing to teach in an effort to maintain health. In the term of special education, adaptive physical education is very necessary in teaching physical education for students with special needs. The main purpose of this study is to determine the perceptions of teachers, especially special teachers, on adaptive physical education in inclusive schools. This study is a descriptive quantitative research involving 15 teachers in Surakarta. Data was collected using questionnaires using 4 Likert scale.The results showed that teachers’ perception on the purpose of adaptive physical education was high for 70%. Meanwhile, teachers’ perception on the implementation of physical adaptive education was high for 62%. However, teachers’ perception on the adaptive physical education materials was moderate for 56%. Also for the assessment in adaptive physical education, teachers’ perception was moderate for 58%. In terms of the physical adaptive education tools, teachers’ perception was high for 81%. The result of this research can be used to develop the nature of adaptive physical education itself, especially in inclusive school. By knowing the teachers’ perceptions on adaptive physical education, some parties can determine which parts are lack and need to be developed, especially in adaptive physical education Keywords: Perception of teachers, adaptive physical education